2023
DOI: 10.1177/10775463231151267
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission loss in functionally graded porous metastructural plate with absorber

Abstract: In the present work, sound transmission loss (STL) of two plates functionally graded sandwich structures with a porous core is studied. The plates are modeled by first-order shear deformation theory. To obtain an acoustic metamaterial plate with the greatest STL, a functionally graded porous (FGP) plate with a tuned mass damper absorber is used. The obtained results show that using a FGP plate or using only an absorber is sufficient for increasing sound transmission loss, but the simultaneous use of them is ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, Choy, Huang, and Wang [11] investigated the possibility of filling porous materials with low-density gas to extend the effective frequency range of sound absorption to lower frequencies and conducted experimental confirmation to support their findings. The research on the sound transmission loss of a two-plate functionally graded sandwich structure with a porous core has demonstrated that the use of FGP plates and absorbers can increase sound transmission loss, and the simultaneous use of both is effective at high frequencies [12]. W.H.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Choy, Huang, and Wang [11] investigated the possibility of filling porous materials with low-density gas to extend the effective frequency range of sound absorption to lower frequencies and conducted experimental confirmation to support their findings. The research on the sound transmission loss of a two-plate functionally graded sandwich structure with a porous core has demonstrated that the use of FGP plates and absorbers can increase sound transmission loss, and the simultaneous use of both is effective at high frequencies [12]. W.H.…”
Section: Introductionmentioning
confidence: 99%